Numerical assessment of microwave imaging for axillary lymph nodes screening using anthropomorphic phantom - Savazzi, M. (2021)
We numerically assess the potential of microwave imaging (MWI) for the detection of axillary lymph nodes (ALNs). The proposed MWI system is radar-based, in which a broad-band signal (2-6 GHz) is transmitted by a single probing antenna to scan the axillary region. The full-wave simulations include a realistic phantom of the underarm region which was previously developed by the authors. The phantom includes the main tissues of the axillary region and the corresponding dielectric properties. We show that the proposed system can successfully detect an ALN embedded in a homogeneous fatty medium. Additionally, we show that despite the strong reflection of the muscle - caused by the high dielectric contrast between fat and muscle - we are able to distinguish an ALN from the background. To the best of our knowledge, this is the first study in literature which employs an anatomically realistic phantom to study ALN MWI.